Effectiveness of Anabolic Steroid Preventative Intervention among Gym Users: Applying Theory of Planned Behavior - Abbas Moghimbeigi; Babak Moeini; Hamid Allahverdipour; Farzad Jalilian (Tabriz University of Medical Sciences, 2011)
Background: Use of anabolic androgenic steroids (AAS) has been associated with adversephysical and psychiatric effects and it is known as rising problem among youth people. Thisstudy was conducted to evaluate anabolic steroids preventative intervention efficiency amonggym users in Iran and theory of planned behaviour was applied as theoretical framework.Methods: Overall, 120 male gym users participated in this study as intervention and controlgroup. This was a longitudinal randomized pretest - posttest series control group design panelstudy to implement a behaviour modification based intervention to prevent AAS use. Cross -tabulation and t-test by using SPSS statistical package, version 13 was used for the statisticalanalysis.Results: It was found significant improvements in average response for knowledge about sideeffects of AAS (P<0.001), attitude toward, and intention not to use AAS. Additionally afterintervention, the rate of AAS and supplements use was decreased among intervention group.Conclusion: Comprehensive implementation against AAS abuse among gym users and adolescenceswould be effective to improve adolescents' healthy behaviors and intend them notto use AAS.